DIETOTHERAPY OF CLASSICAL PHENYLKETONURIA: CRITERIA FOR CHOOSING SPECIALIZED PHENYLALANINE-FREE PRODUCTS - T. E. Borovik; K. S. Ladodo; T. V. Bushueva; A. G. Timofeeva; I. Ya. Kon'; V. I. Kruglik; I. N. Volkova (Вопросы современной педиатрии)
The article contains evidence-based modern criteria for choosing specialized phenylalanine-free foods with L-amino-acids, designed for phenylketonuria treatment in patients of all age groups.